Uterine fibroids: do we deal with more than one disease? - Markowski, Dominique Nadine; Helmke, Burkhard Maria; Bartnitzke, Sabine; Löning, Thomas; Bullerdiek, Jörn (International journal of gynecological pathology, 2014)
Uterine fibroids rank among the most frequent symptomatic human tumors at all. Recent data suggest that mutations of the mediator subcomplex 12 gene (MED12) and rearrangements of the gene-encoding high-mobility group protein AT-hook 2 (HMGA2) characterize major genetic subtypes of these tumors, which, for example, differ by their average size. Herein, we have investigated a total of 289 fibroids from 120 patients. Of these fibroids, 256 were fully genetically analyzed. Of the latter group, 20 (7.8%) fibroids had a chromosomal rearrangement of 12q14-15 reflecting a rearranged allele of HMGA2 and 179 (69.9%) fibroids had a mutation of MED12. The remaining tumors had either another genetic abnormality or no detectable abnormality at all. We were able to demonstrate that tumors of both groups also display striking differences of their frequency in individual patients. Whereas 70.0% (14/20) HMGA2-mutated fibroids made their appearance as solitary nodules, 85.5% (153/179) MED12-mutated fibroids occurred as multiple nodules as a rule of independent clonal origin, as reflected by different MED12 mutations. These findings are likely to point to a different pathogenesis of both types of fibroids. In the predominant of these groups so far, an unknown "mutator" may cause independent mutations of MED12, resulting in an independent clonal outgrowth of nodules. Furthermore, the low but existing risk of MED12-mutated fibroids to undergo malignant transformation after a leiomyoma-STUMP (smooth muscle tumors of uncertain malignant potential)-leiomyosarcoma sequence excludes the latter mutation as a suitable stand-alone marker for benign growth.